University Students’ Perception on the Use E-learning Platforms - Handayani, Fitri; Melvina, Melvina; Sesmiyanti, Sesmiyanti (Yayasan Pendidikan Tanggui Baimbaian, 2025)
This research is based on students’ perceptions of using e- learning platforms in the learning process. The aim of this research is to find out students’ view on how to learn in class using online learning platforms. This research is quantitatif research using English language samples. Research found that English language students were able to adapt to using online e- learning.